Toxicological effect of Artemisinin-Based Combination Therapies plus Paracetamol in malaria patients - S.E. Aghahowa (Elsevier, 2021)
Background: Following the paucity of safety reports in the use of Artemisinin-Based Combination Therapies (ACTs) plus paracetamol, the study assessed safety potential of artemether-lumefantrine (ALP), artesunate-amodiaquine (AAP), artesunate-mefloquine (AMP), artesunate-sulphadoxine-pyrimethamine (ASPP) and dihydroartemisinin-piperaquine (DHPP) combination with paracetamol in malaria patients. Methods: ACTs and paracetamol were administered concomitantly in conventional doses/regimen to randomly selected patients. Blood samples were collected from the ante-cubital vein before and after completion of therapies. Toxicity markers such as weights, glucose, lipids, renal electrolytes, liver enzymes and haematological indices were assessed using standard protocols. Results: The total numbers of participants were 57 patients. Male to female ratio was 1:1.1. Mean body weight and ages were 59.19 ± 1.39 kg and 42.86 ± 1.32 years respectively. The mean temperatures prior to and after therapy were 37.49 ± 1.02 °C and 37.50 ± 0.17 °C respectively. Mean parasitaemia before the commencement of therapy was 6282 ± 21.01 parasites/μl. Out of thirty-seven toxicological indices evaluated, twenty–four were significantly altered by ACTs plus paracetamol (P < 0.05). Increased serum toxicity markers due to the drug combinations were glucose (AAP, AMP), urea (ALP, ASPP), bicarbonate ion (ALP, AAP, AMP, ASPP), chloride ion (ALP, AAP, AMP), creatinine (ALP, AAP, AMP, ASPP), alkaline phosphatase (ALP, AAP), aspartate aminotransferase and alanine aminotransferase (ALP, AAP, AMP, ASPP, DHPP), total protein (AMP, DHPP) and albumin (AMP, DHPP). Decreased serum toxicity markers due to the drugs were glucose (ALP, ASPP, DHPP), urea (AMP), bicarbonate ion (DHPP), chloride ion (ASPP, DHPP), creatinine (DHPP), alkaline phosphatase (AMP, ASPP, DHPP), total protein (ALP, AAP, and ASPP) and albumin (ALP, AAP, ASPP). Altered haematological indices were white blood cells, red blood cells, mean cell haemoglobin and platelets. Conclusion: Since ACTs plus paracetamol altered human system, discrete selection is essential in managing uncomplicated malaria most especially in patients with co-morbid conditions.